Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada PT Pegadaian Persero Kantor Cabang Bekasi Timur - Putri Rachmawati; Kardinah Indrianna Meutia; Nita Komala Dewi (Universitas Kristen Indonesia Toraja, 2024)
This research aims to measure the influence of work discipline and work motivation on employee performance at PT Pegadaian Persero East Bekasi Branch Office. This research was conducted using quantitative methods. The number of samples used in this research was 50 respondents. The design used in this research is hypothesis testing using SPSS Versi 25. The results of this research show that (1) There is no correlation between Work Discipline and Employee Performance; (2) There is a correlation between work motivation and employee performance; (3) There is a correlation between Work Discipline and Work Motivation on Employee Performance.